HILL, William Henry Rowlands Inventory of documents - HILL, William Henry Rowlands (ARCA, 2018)
Private papers of W.H.R. Rowlands, journalist at The Nation [1924-1925], Assistent Editor of the Natal Mercury [1925-1934], columnist of The Cape Times[ 1934-1965]
COVERAGE 1952; 1 File; 0.11 metre
Keywords: HILL, William Henry Rowlands; Journalist